THE ROLE OF SAP BUSINESS OBJECT TO SUPPORT A BUSINESS INTELLIGENCE PERFORMANCE - Abadi, Eileen Fransisca; Terziev, Aleksandar; Setiawan, Alexander (Institute of Research and Community Outreach - Petra Christian University, 2017)
As the world of information and communication technology grows, it is becoming increasingly important for the role of technology as the primary information processor in every line of human life today. It can be concluded that the current role of technology has evolved into needs, not just corporate or academic interests. This creates the birth of a new economy marked by the high penetration of the use of IT (Information Technology) in the business transaction process, so the concept evolves into a smart business, thus improving business performance. So the concept of SAP Business Object to be applied this can help improve the company's performance to continue to innovate on an ongoing basis.